Guidelines for a Polycentric Region to Reduce Vehicle Use and Increase Walking and Transit Use. Issue 2 (2nd April 2020) - Park, Keunhyun; Ewing, Reid; Sabouri, Sadegh; Choi, Dong-ah; Hamidi, Shima; Tian, Guang
Abstract: Problem, research strategy, and findings: The monocentric development pattern in the Alonso–Mills–Muth model underpinned theoretical discussions of urban form in the 1960s and 1970s and truly dominated theory up to the point when Joel Garreau published Edge City: Life on the New Frontier in the early 1990s. Monocentric development patterns remain dominant to this day among smaller metropolitan areas in the United States. However, for larger metropolitan areas in the United States, regional transportation plans suggest a paradigm shift to a polycentric structure. We review 126 regional transportation plans in the United States and find that a hierarchy of centers connected by high-quality transit has become the dominant vision for most of them. The plan for Salt Lake City (UT), for example, strives for a multicentered region even though secondary centers are only beginning to emerge beyond a dominant downtown. Generally missing from regional transportation plans are quantitative criteria for designating and guiding centers: In no case are the quantitative criteria empirically based on proven transportation benefits. Here we investigate how the built environment characteristics of centers are associated with people's travel mode choices and vehicle use. We employ visual and exploratory approaches through a generalized additive model (GAM) to identify nonlinear relationships between travel outcomes and "D" variables (density, diversity, design, destination accessibility, and distance to transit) within centers. The model and plots help us recommend the built environment characteristics of centers. Takeaway for practice: The built environment thresholds and relevant tools provided here can enable planners to make informed decisions about future growth patterns, set realistic—yet visionary—goals, and improve the overall health of its residents and communities. We provide strategies and tools that planning agencies, such as metropolitan planning organizations, transit agencies, and municipalities, can adopt to channel developments into centers.